Peran Mediasi Financial Behavior: Income, Financial Literacy, dan Digital Literacy terhadap Investment Decisions pada Generasi Z di Kota Semarang - Izha Rachma Navila; Fakhmi Zakaria; Dwi Eko Waluyo; Dian Prawitasari (Pusat Riset dan Inovasi Nasional, 2026)
Although 55.07% of capital market investors are under 30 years old and IMDI in Semarang City is very high (58.59), approximately 20-30% of Generation Z still demonstrate suboptimal levels of financial literacy, digital literacy, financial behavior, and investment decision making. This study aims to analyze the influence of income, financial literacy, and digital literacy on investment decisions with financial behavior as a mediating variable among Generation Z in Semarang City. The research method used a quantitative approach with purposive sampling of 115 respondents and was analyzed using PLS-SEM through SmartPLS 4.0. The results show that financial literacy and digital literacy have a significant positive effect on financial behavior and investment decisions, financial behavior has a significant positive effect on investment decisions, and is able to mediate the influence of financial literacy and digital literacy, but income has no effect either directly or through the mediation of financial behavior.